Diseminasi Pendidikan Moderasi Islam Pada Mahasiswa: Strategi Menangkal Radikalisme di Perguruan Tinggi Umum (The Dissemination of Moderate Islamic Education to Students: Strategies to Counter Radicalism in Public University) - Iis Sugiarti; Moh Roqib (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACT The crucial phenomenon that is the background of this research is the strengthening of the seeds of radicalism in Public Universities. The academic community, such as lecturers and students, are not spared from being influenced by extremist-radicalist notions, even in the context of the University of Djendral Sudirman (Unsoed) Purwokerto, there are lecturers who are members of the ISIS network and several students who are members of the NII network. Therefore, it is important for higher education institutions to internalize religious moderation (wasathiyyah) to students, so as to form a moderate religious attitude and not easily influenced by extremist-radicalist religious understandings. The purpose of writing this article is to discover patterns of religious understanding of Unsoed Purwokerto students and strategies for internalizing Islamic moderation values to students to counteract radicalism. This article is field research with a qualitative-descriptive approach and uses observation, interview and documentation techniques in searching the data. The results of the study indicate that the pattern of religious understanding of Unsoed Purwokerto students tends to be not comprehensive. The process of internalizing the value of Islamic moderation to students is carried out through PAI courses, lecturer approaches in teaching (dialogical, rational, and anthropological), fostering Al-Qur'an Reading and Writing and interpretation and mentoring through the Islamic Religious Assistance Program (P2AI). The strategies to counter radicalism are providing national insight in collaboration with the TNI-POLRI, forming SMEs that are adaptive to culture and the arts, socialization and dialogue about terrorism and radicalism with the National Counter-Terrorism Agency, Campus News, providing an understanding of religious moderation in the academic community, legalizing extra organizations to have activities on campus internally, accommodating courses for Believers, and carry out nationalism internalization through Unsoed Identity and Civics Courses. Keywords: Islamic Moderation; Students; Public University; RadicalismABSTRAKFenomena krusial yang menjadi latar belakang penelitian ini adalah menguatnya benih-benih radikalisme di Perguruan Tinggi Umum. Civitas akademika, seperti dosen dan mahasiswa tidak luput terpengaruh oleh paham eksremis-radikalis, bahkan dalam konteks di Universitas Djendral Soedirman (Unsoed) Purwokerto terdapat dosen yang tergabung dalam jaringan ISIS dan beberapa mahasiswa yang masuk ke dalam jaringan NII. Oleh karena itu, menjadi penting Perguruan Tinggi melakukan internalisasi moderasi beragama (wasathiyyah) kepada mahasiswa, sehingga membentuk sikap keberagamaan yang moderat dan tidak mudah terpengaruh oleh pemahaman agama ektremis-radikalis. Tujuan penulisan artikel ini adalah untuk menemukan pola pemahaman keagamaan mahasiswa Unsoed Purwokerto dan strategi internalisasi nilai moderasi Islam kepada mahasiswa untuk menangkal radikalisme. Artikel ini merupakan penelitian lapangan dengan pendekatan kualitatif-deskriptif dan menggunakan teknik observasi, wawancara dan dokumentasi dalam pencarian datanya. Adapun hasil penelitian menunjukkan bahwa pola pemahaman keagamaan mahasiswa Unsoed Purwokerto cenderung tidak komprehensif. Proses internalisasi nilai moderasi Islam pada mahasiswa dilaksanakan melalui mata kuliah PAI, pendekatan dosen dalam mengajar (dialogis, rasional, dan atropologis), pembinaan Baca Tulis al-Qur’an dan tafsir serta mentoring melalui Program Pendampingan Agama Islam (P2AI). Adapun strategi untuk menangkal radikalisme yaitu memberikan wawasan kebangsaan bekerja sama dengan TNI-POLRI, membentuk UKM yang adaptif dengan budaya dan seni, sosialisasi dan dialog tentang terorisme dan radikalisme bersama Badan Nasional Penanggulangan Terorisme, Kampus Mengaji, memberikan pemahaman moderasi beragama pada civitas akademika, melegalkan organisasi ekstra beraktivitas di dalam internal kampus, mengakomodir mata kuliah bagi Penghayat Kepercayaan, dan melakukan internalisasi kebangsaan melalui mata kuliah Jati Diri Unsoed dan PKn.Kata kunci: Moderasi Islam; Mahasiswa; Perguruan Tinggi Umum; Radikalisme.